A human-relevant alternative infection model for mucormycosis using the silkworm Bombyx mori - Masaki Ishii; Kazuhiro Mikami; Fumiaki Tabuchi; Naho Maruyama; Atsushi Miyashita (PLoS ONE, 2025)
Mucorales fungi cause life-threatening mucormycosis in patients with clinical risk factors, such as immunodeficiency. Moreover, they are resistant to several antifungal drugs, highlighting the urgent need for novel therapies. Traditional mammalian models are expensive and raise ethical concerns, thereby limiting their suitability for large-scale studies. We established a silkworm (Bombyx mori) infection model to investigate the pathogenicity of Mucorales and evaluated its relevance to human infection. Strains of Rhizopus arrhizus, Mucor circinelloides, and Cunninghamella bertholletiae induced fatal infections in the silkworm. Grocott-stained silkworm tissue sections revealed hyphal invasion patterns closely resembling those observed in human mucormycosis. In addition, experimental simulation of clinical risk factors (steroid use and iron overload) significantly reduced the median lethal dose (LD50). Treatment with the antifungal drug isavuconazonium prolonged the survival of R. arrhizus-infected silkworms, suggesting the potential use of this model for novel antifungal screening. LD50 estimation for four R. arrhizus strains revealed up to a 100-fold difference in pathogenicity to the silkworm among the tested strains, corresponding to variations in cell surface characteristics. Interestingly, the presence of high-molecular weight (50–100 kDa) cell surface proteins was associated with high pathogenicity among R. arrhizus strains. In conclusion, the silkworm is a viable, human-relevant alternative model to investigate Mucorales infections, with potential for large-scale antimucormycosis drug screening.